LC-MS/MS quantitative analysis of phylloquinone, menaquinone-4 and menaquinone-7 in the human serum of a healthy population - Dunovska, Katerina; Klapkova, Eva; Sopko, Bruno; Cepova, Jana; Prusa, Richard (PeerJ, 2019)
A novel application of the liquid chromatography method combined with the triple quadrupole tandem mass spectrometry method was developed for the quantification of vitamin K1 and two forms of vitamin K2 (menaquinone-4, menaquinone-7) in human serum. Total chromatography time for each run was 9 min. Time required for the sample pretreatment procedures was approximately 4 h. The coefficients of variation (CVs) of intra-assay were 10.4%, 3.2 % and 2.3% for vitamin K1 in three levels of quality control samples; were 14.3%, 3.2% and 6.7% for menaquinone-4; and were 11.1%, 6.0% and 7.0% for menaquinone-7. The inter-assay CVs were 12.8%, 11.3% and 7.4% for vitamin K1; were 15.2%, 9.2% and 8.7% for menaquinone-4; and were 13.2%,11.1% and 7.2% for menaquinone-7. No interference was found between K1, menaquinone-4 and menaquinone-7, nor any deuterated internal standards. This method was then used to determine reference values for Caucasian populations of central European origin. Samples were measured from 191 healthy volunteers (51.2 ± 16.2 years (mean ± SD)) and the values concerning K1 were 0.044-1.357 ng/mL for women and 0.030-1.214 ng/mL for men. The values for menaquinone-4 and menaquinone-7 did not exhibit any differences between women and men, and were 0.050-1.598 and 0.074-0.759 ng/mL, respectively.
Keywords: Menaquinone; Phylloquinone; Deuterated internal standard; LC–MS/MS